Alternative strategies to increase the immunogenicity of COVID-19 vaccines in kidney transplant recipients not responding to two or three doses of an mRNA vaccine (RECOVAC): a randomised clinical trial. Issue 3 (March 2023) - Kho, Marcia M L; Messchendorp, A Lianne; Frölke, Sophie C; Imhof, Celine; Koomen, Vera JCH; Malahe, S Reshwan K; Vart, Priya; Geers, Daryl; de Vries, Rory D; GeurtsvanKessel, Corine H; Baan, Carla C; van der Molen, Renate G; et al.
Summary: Background: An urgent need exists to improve the suboptimal COVID-19 vaccine response in kidney transplant recipients (KTRs). We aimed to compare three alternative strategies with a control single dose mRNA-1273 vaccination: a double vaccine dose, heterologous vaccination, and temporary discontinuation of mycophenolate mofetil or mycophenolic acid. Methods: This open-label randomised trial, done in four university medical centres in the Netherlands, enrolled KTRs without seroconversion after two or three doses of an mRNA vaccine. Between Oct 20, 2021, and Feb 2, 2022, 230 KTRs were randomly assigned block-wise per centre by a web-based system in a 1:1:1 manner to receive 100 μg mRNA-1273, 2 × 100 μg mRNA-1273, or Ad26.COV2-S vaccination. In addition, 103 KTRs receiving 100 μg mRNA-1273, were randomly assigned 1:1 to continue (mycophenolate mofetil+) or discontinue (mycophenolate mofetil-) mycophenolate mofetil or mycophenolic acid treatment for 2 weeks. The primary outcome was the percentage of participants with a spike protein (S1)-specific IgG concentration of at least 10 binding antibody units per mL at 28 days after vaccination, assessed in all participants who had a baseline measurement and who completed day 28 after vaccination without SARS-CoV-2 infection. Safety was assessed as a secondary outcome in all vaccinated patients by incidence of solicited adverse events, acute rejection or other serious adverse events. This trial is registered with ClinicalTrials.gov, NCT05030974 and is closed. Findings: Between April 23, 2021, and July 2, 2021, of 12 158 invited Dutch KTRs, 3828 with a functioning kidney transplant participated in a national survey for antibody measurement after COVID-19 vaccination. Of these patients, 1311 did not seroconvert after their second vaccination and another 761 not even after a third. From these seronegative patients, 345 agreed to participate in our repeated vaccination study. Vaccination with 2 × mRNA-1273 or Ad26.COV2-S was not superior to single mRNA-1273, with seroresponse rates of 49 (68%) of 72 (95% CI 56–79), 46 (63%) of 73 (51–74), and 50 (68%) of 73 (57–79), respectively. The difference with single mRNA-1273 was -0·4% (-16 to 15; p=0·96) for 2 × mRNA-1273 and -6% (-21 to 10; p=0·49) for Ad26.COV2-S. Mycophenolate mofetil- was also not superior to mycophenolate mofetil+, with seroresponse rates of 37 (80%) of 46 (66–91) and 31 (67%) of 46 (52–80), and a difference of 13% (-5 to 31; p=0·15). Local adverse events were more frequent after a single and double dose of mRNA-1273 than after Ad26.COV2-S (65 [92%] of 71, 67 [92%] of 73, and 38 [50%] of 76, respectively; p<0·0001). No acute rejection occurred. There were no serious adverse events related to vaccination. Interpretation: Repeated vaccination increases SARS-CoV-2-specific antibodies in KTRs, without further enhancement by use of a higher dose, a heterologous vaccine, or 2 weeks discontinuation of mycophenolate mofetil or mycophenolic acid. To achieve a stronger response, possibly required to neutralise new virus variants, repeated booster vaccination is needed. Funding: The Netherlands Organization for Health Research and Development and the Dutch Kidney Foundation.